Paradoxes and tensions in interorganizational relationships: A systematic literature review - Marcos Vinícius Bitencourt Fortes; Lara Agostini; Douglas Wegner; Anna Nosella (Journal of Risk and Financial Management, 2023)
This paper examines the literature on paradoxes and tensions in interorganizational relationships (IORs) and identifies how such tensions are managed in interorganizational settings. In a systematic literature review, we analyzed 95 papers published between 1997 and 2021 on the subject of paradoxes in IORs. The sample showed a variety of paradoxes occurring in different interorganizational contexts, such as knowledge sharing and protection, short- and long-term orientation, and exploration and exploitation. The diversity of such paradoxes has led to crescent interest in cooperation. Our main results show that contextual factors and management practices influence the balance between paradoxes. Although the particular context of each IOR may be unique in terms of balancing paradoxical elements, we identified a set of "pre-tension practices" and "post-tension practices" which may help avoid the emergence of tensions or reduce their adverse effects. The findings of our systematic literature review have also enabled us to propose future research avenues concerning managing tensions in IORs, for instance, the link between paradoxes and IOR performance.
Keywords: 650; paradox; interorganizational relationship; tension; tension management